2006
DOI: 10.1002/hbm.20314
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosal connection mapping using cortical gray matter parcellation and DT‐MRI

Abstract: Population maps of the corpus callosum (CC) and cortical lobe connections were generated by combining cortical gray matter parcellation with the diffusion tensor fiber tractography of individual subjects. This method is based on the fact that the cortical lobes of both hemispheres are interconnected by the corpus callosal fibers. T1-weighted structural MRIs and diffusion tensor MRIs (DT-MRI) of 22 right-handed, healthy subjects were used. Forty-seven cortical parcellations in the dorsal prefrontal cortex, vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(179 citation statements)
references
References 53 publications
10
160
0
1
Order By: Relevance
“…According to results of our study, the relative mean distances of the highest probabilistic locations for the precentral knob PMC, hand M1, leg M1, and precentral knob S1 TCF were to results of previous DTI studies [13][14][15][16]20].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…According to results of our study, the relative mean distances of the highest probabilistic locations for the precentral knob PMC, hand M1, leg M1, and precentral knob S1 TCF were to results of previous DTI studies [13][14][15][16]20].…”
Section: Resultssupporting
confidence: 75%
“…By contrast, recent advancements in diffusion tensor tractography (DTT), derived from DTI, have now allowed visualization of the architecture and integrity of TCF in three dimensions [8][9][10][11]. Many DTT studies have reported on the topography of TCF [12][13][14][15][16][17][18][19][20][21]. However, little is known about detailed anatomical information on TCF that can be easily applied for clinical purposes [14,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable variation in metacognitive accuracy (using type 2 SDT analysis) was found despite task performance remaining constant across individuals. Through use of structural brain imaging, this variance in metacognitive accuracy was shown to positively correlate with grey matter volume in right rlPFC (BA10; peak: 24, 65, 18; figure 4a), and greater metacognitive accuracy was associated with increased white matter integrity (fractional anisotropy) in a region of the corpus callosum known to project to the rlPFC [97]. Such findings are consistent with individual differences in localized brain structure affecting a region's functional properties [98].…”
Section: Neural Basis Of Metacognitive Accuracy (A) Studies Of Metamementioning
confidence: 54%
“…Fourth, structural connections between CC activation and gray matter activation may be difficult to detect in regions that have other large tracts coursing in different orientations. For example, fibres from the internal capsule and inferior longitude fasciculus may cross the callosal fibres that connect the temporal lobes (Park et al, 2008). This issue may be overcome by using advanced acquisition and analysis techniques (e.g., diffusion spectrum imaging; Wedeen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%